Optic Disc Structural, Vascular and Functional Assessment in Patients with Primary Raynaud’s Phenomenon - Carreira, Ana Rita (2022)
INTRODUCTION: Our aim was to assess optic disc structural, vascular and functional parameters in patients with primary Raynaud’s phenomenon (PRP). METHODS: This study enrolled patients with PRP and healthy age-matched controls. Subjects underwent evaluation of intraocular pressure (IOP), anterior chamber angle, optic disc structural and vascular parameters (measured by optical coherence tomography) and visual field. RESULTS: Twenty-four eyes were included in the control group, with a mean age of 44.20 ± 4.67 years, and 20 eyes in the PRP group, with a mean age of 43.00 ± 6.08 years (p=0.20). Inferior and nasal retinal nerve fiber layer (RNFL) thickness was lower in PRP group (104.05 ± 17.64 vs 118.67 ± 12.60μm, p=0.01; 70.05 ± 12.21 vs 79.50 ± 12.70 μm, p=0.04, respectively). Vascular density was lower in PRP group, mostly in the inner ring (15.90 ± 2.10 vs 14.20 ± 0.43 mm-1, p=0.02). No difference was found in functional parameters (p>0.05). No correlation was found between optic disc vascular density and RNFL thickness on multivariate regression analysis (p>0.05). CONCLUSION: Our findings suggest that PRP may possibly negatively affect the optic nerve, with a reduced vascular density and RNFL thickness.